Inferring personal economic status from social network location - Shaojun Luo (Nature Portfolio, 2017)
It is believed that patterns of social ties are related to individuals’ financial status. Here the authors substantiate this concept by quantitatively demonstrating that a measure of an individual’s location and influence within their social network can be used to infer their economic wellness.